Spatializing Narrative: Postcolonial Spaces of Oswald Andrew Bushnell’s Ka’a’awa - Kristiawan Indriyanto (Universitas Sanata Dharma, 2023)
This study explores the representation of space in O.A Bushnell’s Ka’awa in which the seemingly contradictory spatial scene of the urban, the rural, the picturesque and the macabre delineates the complexity of postcolonial spaces. Ka’a’awa foregrounds the journey of Hiram Nihoa through his travel all around O’ahu in the 1850’s. Nihoa’s first-person account provides a vivid avenue for the readers through textual cues delineating spaces as they mentally mapped the slowly unfolding and unfamiliar spaces as his narration progresses. This study is the intersection between environmental/eco-criticism and geo-criticism which focuses on the complexities between spatial referents and their real-world referents as is stated by Tally Jr and Prieto, especially the postcolonial contexts of Hawai’i-West interaction during the second half of the 19th century. The finding posits how the readers familiarize themselves with the picturesque landscape of O’ahu through Nihoa’s evocative narration and how the spatial scene later resurfaces as space connotes death and diseases due to epidemic which defamiliarizes readers from prior spatiality. The spatial scene narrating scene of disease, despair and death highlights the discursive and material condition of Hawai’i as a postcolonial space. Space in Ka’a’awa alludes both toward the referential condition of 1850’s Hawai’i and symbolically represents the decline of the Hawai’ian natives.